Impact of vitamin D replacement in adults and elderly in the Middle East and North Africa: a systematic review and meta-analysis of randomized controlled trials. Issue 1 (January 2017) - Chakhtoura, M.; Akl, E.; El Ghandour, S.; Shawwa, K.; Arabi, A.; Mahfoud, Z.; Habib, R.; Hoballah, H.; El Hajj Fuleihan, G.
Abstract Summary In the Middle East and North Africa (MENA), a vitamin D dose ≥2000 IU/day may be needed to allow to the majority of the population to reach the target 25-hydroxyvitamin D (25(OH)D) level ≥20 ng/ml. Data in the region on the effect of vitamin D supplementation on various skeletal and extra-skeletal effects are scarce. Introduction Hypovitaminosis D is prevalent worldwide, more so in the Middle East and North Africa (MENA). This study aims to determine the effects of vitamin D replacement on the mean difference in 25-hydroxyvitamin D [25(OH)D] level reached and other outcomes, in the MENA. Methods This is a meta-analysis of randomized trials from the MENA, administering vitamin D supplementation for at least 3 months, without language or time restriction. We conducted a comprehensive search in seven databases until July 2015. We abstracted data from published reports, independently and in duplicate. We calculated the mean difference (MD) and 95 % CI of 25(OH)D level reached for eligible comparisons, and pooled data using RevMan version 5.3. Results We identified 2 studies in elderly and 17 in adults; for the latter, 11 were included in the meta-analysis. Comparing a high vitamin D dose (>2000 IU/day) to placebo (nine studies), the MD in 25(OH)D level achieved was 18.3 (CI 14.1; 22.5) ng/ml;p value < 0.001;I 2 = 92 %. Comparing an intermediate dose (800–2000 IU/day) to placebo (two studies), the MD in 25(OH)D level achieved was 14.7 (CI 4.6; 24.9) ng/ml;p value 0.004;I 2 = 91 %. Accordingly, 89 and 71 % of participants, in the high and intermediate dose groups, respectively, reached the desirable level of 20 ng/ml. The risk of bias in the included studies was unclear to high, except for three studies. Conclusion In the MENA region, vitamin D doses ≥2000 IU/day may be needed to reach the target 25(OH)D level ≥20 ng/ml. The long-term safety and the efficacy of such doses on various outcomes are unknown.